SÖZLÜ TARİH/SÖZLÜ GELENEK VE HADİS KİTAPLARI-Sahîh-i Müslim Örneği- - M. Hanefi Palabıyık (İslami İlimler Dergisi)
As the Quran shows the characteristic of oral message/narrative tradition; the historical and the hadith texts also show the same characteristics extremely. This paper studies Sahîh-i Muslim, the most well-known and reliable hadith book, and also researches on it in point of the characteristic of oral message/narrative tradition. We have thought of giving an example of ‘Kitâbu’l- Imân’, the longest and first part of Sahîh-i Muslim. This study is done for the purpose of stressing on disregarding of oral message/narrative tradition in the hadith researches. We have thought that the examples we give in the study are enough to comprehend whole Sahîh-i Muslim and all the other hadith books. Here are the some results gained: The most important problem of these texts is that they have no a context generally. The event explained in the text certainly loses the liveliness and meaningfulness in the world of first relaters. The hadiths we have as a written text now comprise all the weakness of a written text. In order that the confidence is up to the relater in a narrative culture, and also because of the complete narratives accepted in the classical period are texts now, the criterions of understanding and commenting upon it have changed. What’s more, the classical understanding methods can be added to this. Although these texts are indited from the beginning, we think that the natural and the sceptic attitude for the writing and the text and the book include the hadith texts too. The narration of the events taking place in natural context and mediocrity in the life of Prophet Muhammad had turned into the juristic rule and the legitimate evidence. By conducing to the ideological use of hadiths, this attitude also caused the literalism and the fictitious hadiths. Along with this, we want to emphasize that written sources formed by the oral tradition should be revised critically and used together with the all sources reached; in other words, the main principles of the historical method should are acceptable here. As accepting by agreement in the Islamic thought tradition, the beginning forms of narrations forming the peak of oral tradition, stories, biography of Prophet Muhammad, campaign of Prophet Muhammad, historical texts, hadith texts and commentary texts are the helpers of history as a whole.